2003
DOI: 10.1021/jo030123c
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Carbapenam by Intramolecular Attack of Lactam Nitrogen toward η1-Allenyl and η3-Propargylpalladium Complex

Abstract: When a THF solution of beta-lactam having propargyl phosphate was warmed in the presence of 5 mol % of Pd(2)(dba)(3) x CHCl(3), 20 mol % of a bidentate ligand, and sodium acetate (1.5 equiv) at 40 degrees C for 22 h, carbapenam was produced in high yield. In this reaction, the lactam nitrogen attacked the central carbon of a eta(3)-propargylpalladium complex, which was formed from propargyl phosphate and Pd(0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Chemie to generate an allenylpalladium complex 5; [13,14] b) regioselective intramolecular nucleophilic attack of the carbanion to form intermediate 4 a; c) oxidative addition of the aryl halide to the palladium(0) catalyst; d) the addition of arylpalladium compounds to 1,2-dienes produces p-allylpalladium compounds; [15] and e) regioselective intramolecular nucleophilic attack [14] at the more hindered site to afford products 3. [16] The selectivity is presumably due to electronic effects [8a, 9c] at the benzylic position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemie to generate an allenylpalladium complex 5; [13,14] b) regioselective intramolecular nucleophilic attack of the carbanion to form intermediate 4 a; c) oxidative addition of the aryl halide to the palladium(0) catalyst; d) the addition of arylpalladium compounds to 1,2-dienes produces p-allylpalladium compounds; [15] and e) regioselective intramolecular nucleophilic attack [14] at the more hindered site to afford products 3. [16] The selectivity is presumably due to electronic effects [8a, 9c] at the benzylic position.…”
Section: Methodsmentioning
confidence: 99%
“…We have also investigated the reactions of substrates having various leaving groups. The reactions of propargyl carbonate 1 b, propargyl acetate 1 c and propargyl benzoate 1 d gave the desired products 3 a in moderate yields ( Table 2, entries [12][13][14]. In addition, propargyl phosphate 1 e also gave the product 3 a in a 62 % yield and shorter reaction time was required ( Table 2, entry 15).…”
mentioning
confidence: 99%
“…1,2 Many of the reports on the reactions describe the synthesis of heterocyclic compounds. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Sinou and coworkers [19][20][21][22] reported a palladiumcatalyzed condensation reaction of propargylic carbonates and catechol for the synthesis of 1,4-benzodioxins. When the reaction was performed with methyl-substituted carbonates 1a and 2a, the same product was obtained in 95% yield [Scheme 1(a)].…”
mentioning
confidence: 99%
“…It has been found that other amines, such as benzylamine, naphthalen-2-amine and furan-2-amine were also well tolerated under our conditions (entries 10 and 12). We have also investigated the reactions of substrates with various leaving groups, such as propargyl acetate 1b, propargyl benzoate 1c and propargyl acetate 1d afforded the desired products 3a in good yields (entries [13][14][15].…”
mentioning
confidence: 99%
“…(i) Decarboxylation of propargylic compound 1 catalyzed by Pd (0) generates an allenylpalladium complex 4 [13] or the Ni(II) species coordinates with the alkyne triple bond of 1 to afford 6. (ii) Base mediates a Michael addition which affords intermediate 5 or 7, respectively.…”
mentioning
confidence: 99%